Proceedings. International Symposium on Information Theory, 2005. ISIT 2005. 2005
DOI: 10.1109/isit.2005.1523376
|View full text |Cite
|
Sign up to set email alerts
|

Memory-efficient decoding of LDPC codes

Abstract: We present a low-complexity quantization scheme 1 for the implementation of regular (3, 6) LDPC codes. The quantization parameters are optimized to maximize the mutual information between the source and the quantized messages. Using this non-uniform quantized belief propagation algorithm, we have simulated that an optimized 3-bit quantizer operates with 0.2dB implementation loss relative to a floating point decoder, and an optimized 4-bit quantizer operates less than 0.1dB quantization loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 5 publications
0
58
0
1
Order By: Relevance
“…To implement LDPC decoders on integrated circuits, all of the messages will be quantized into bits. Existing studies [20] have shown that 4-6 bits' quantization on messages can provide ideal compromise between complexity and performance for LDPC decoders. Among the quantized bits, one is used for the sign, while the rest are used for the magnitude value.…”
Section: Ldpc Decodermentioning
confidence: 99%
See 2 more Smart Citations
“…To implement LDPC decoders on integrated circuits, all of the messages will be quantized into bits. Existing studies [20] have shown that 4-6 bits' quantization on messages can provide ideal compromise between complexity and performance for LDPC decoders. Among the quantized bits, one is used for the sign, while the rest are used for the magnitude value.…”
Section: Ldpc Decodermentioning
confidence: 99%
“…However, TMR will charge two extra bits for protecting the sign bit while the messages are typically quantized into only 4 to 6 bits [20]. As a result, if we maintain the quantity of message quantization bits under the constraint of complexity, introducing TMR will bring a loss of quantization precision, which is not always beneficial for various storage error ratios.…”
Section: Triple Modular Redundancy Scheme For Sign Bit Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many significant works related to the design and analysis of quantized decoders as well as lowcomplexity implementations of BP-based decoders. Some of the notable works include (but not limited to) the quantized decoders (such as Gallager-E) proposed by Richardson and Urbanke [10], low-complexity BP decoders by Chen et al [20], and by Fossorier, Mihaljevic and Imai [21], quantized BP decoders by Lee and Thorpe [22], and quantized minsum decoders by Smith, Kschischang and Yu [23]. A key distinction that is to be noted between our approach and all these aforementioned works is that their primary objective is to approach BP rather than outperform BP, since they are all based on asymptotic analytical methods.…”
Section: A Quantized Message-passing Decodersmentioning
confidence: 99%
“…A large quantization step leads to severe quantization distortion and degrades the performance of decoding, while a small dynamic range yields serious quantization overflow and hence a high error floor. Only non-uniform quantization can balance the requirements between the quantization step and dynamic range [8][9][10] . The optimal non-uniform quantization scheme depends on the distribution of messages, but the distribution varies with the number of iterations.…”
Section: Introductionmentioning
confidence: 99%